تكفير أهل الشهادتين وعلاقتها بقاعدة اليقين لا يزول بالشك والآثار الدينية المترتبة عليهم - Dzulfikar Syam; Imron Rosyadi; M. Muinudinillah (Universitas Muhammadiyah Surakarta, 2019)
Abstract: There is no doubt that the science of qowaid fiqh is a different science from that of aqidah, because the contents of the former are different. Aqidah knowledge discusses matters of iman and ghaib, as for the science of qowaid fiqh is about the case of rules or dhowabit and laws of Shariat. But it is undeniable that there are some principles of fiqh relating to matters of iman, including the laws about takfir (sentencing kaafir). Among the basic principles of fiqh is